2012
DOI: 10.1016/j.jacc.2011.09.078
|View full text |Cite|
|
Sign up to set email alerts
|

Morphometric Assessment of Coronary Stenosis Relevance With Optical Coherence Tomography

Abstract: OCT has a moderate diagnostic efficiency in identifying hemodynamically severe coronary stenoses. Although OCT seems slightly superior to IVUS for this purpose (particularly in vessels <3 mm), its low specificity precludes its use as a substitute of FFR for functional stenosis assessment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

9
87
1
3

Year Published

2012
2012
2018
2018

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 188 publications
(100 citation statements)
references
References 24 publications
9
87
1
3
Order By: Relevance
“…8 Previous reports using IVUS-derived MLA to assess myocardial ischemia are summarized in Table 3. 7-13,26, 27 The accuracy of IVUS-derived MLA to identify functional ischemia ranged from 66% to 79%. Thus, IVUS-derived MLA is limited in accuracy.…”
Section: Discussionmentioning
confidence: 99%
“…8 Previous reports using IVUS-derived MLA to assess myocardial ischemia are summarized in Table 3. 7-13,26, 27 The accuracy of IVUS-derived MLA to identify functional ischemia ranged from 66% to 79%. Thus, IVUS-derived MLA is limited in accuracy.…”
Section: Discussionmentioning
confidence: 99%
“…They found no significant correlation between FFR and the OCT measured MLA (r = 0.167, P = 0.56), MLD (r = -0.42, P = 0.13), and %AS (r = 0.29, P = 0.29). Recently, Gonzalo, et al 19) evaluated the diagnostic efficiency of OCT derived lumen measurements in identifying the stenosis severity in 56 patients with 61 stenoses. They reported poor but significant correlation between FFR and OCT measured MLA (r = 0.51, P < 0.001), MLD (r = 0.4, P = 0.005), and %AS (r = 0.33, P = 0.02).…”
Section: Discussionmentioning
confidence: 99%
“…Its higher spatial resolution may offer much clearer identification of the lumen border, but very little data are available concerning the efficacy of OCT findings in assessing the significance of a stenosis. 12 In this issue of the Journal, Shiono et al 13 attempt to address this issue by comparing OCT findings with FFR. They found that MLA, minimum lumen diameter (MLD) and percent lumen area stenosis measured by OCT correlated well with FFR values; the best cutoff values measured by OCT to identify stenoses with Anatomical and Functional Assessments of Stenosis FFR <0.75 were 1.91 mm 2 , 1.35 mm and 70.0%, respectively.…”
Section: Article P 2218mentioning
confidence: 99%
“…However, using frequency-domain OCT, the optimal cutoff value of MLA to predict FFR <0.80 was determined to be 1.95 mm 2 , which was also lower than the IVUS-derived cutoff value. 12 There appear to be fundamental differences between the OCT and IVUS measurements of MLA.…”
Section: Article P 2218mentioning
confidence: 99%